The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Handbook of Learning Analytics 2017
DOI: 10.18608/hla17.019
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modelling of Student Behavior Using Granular Large-Scale Action Data

Abstract: Digital learning environments generate a precise record of the actions learners take as they interact with learning materials and complete exercises towards comprehension. With this high quantity of sequential data comes the potential to apply time series models to learn about underlying behavioral patterns and trends that characterize successful learning based on the granular record of student actions. There exist several methods for looking at longitudinal, sequential data like those recorded from learning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Within a set time period of one week, various representative values were calculated to summarize a learner's behavior. We constructed twelve features, most of which were taken from a thoroughly-described set of features of a similar experiment by [13], but with week-by-week comparison features removedwhile [13] predicted when a learner would drop-out, we are focusing on if the learner eventually receives certification. To account for the loss of information about how far a learner has progressed through the course, we included two extra features not included in [13] (see features 6 and 12 in Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a set time period of one week, various representative values were calculated to summarize a learner's behavior. We constructed twelve features, most of which were taken from a thoroughly-described set of features of a similar experiment by [13], but with week-by-week comparison features removedwhile [13] predicted when a learner would drop-out, we are focusing on if the learner eventually receives certification. To account for the loss of information about how far a learner has progressed through the course, we included two extra features not included in [13] (see features 6 and 12 in Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Very few studies have combined predictive modeling with real-world interventions in a MOOC. In [20], next resource suggestions were made using a predictive model of behavior [19]. On residential campuses, predictive models of drop-out have been operationalized in the form of dispatching counselors for flagged students [18], an approach which can have unintended side effects of signaling to students that they are not likely to pass the course, and thus catalyzing a greater rate of drop-out than without the intervention.…”
Section: Related Workmentioning
confidence: 99%
“…The novel intuition of our application of this to student course sequences is that instead of learning the structure of language by training on sequences of words, we are learning the structure of learner behaviour from sequences of page views. It was previously found that clickstream behaviours within MOOCs could be predicted using a Recurrent Neural Network (RNN) with 70% accuracy, compared to the 45% accuracy provided by the expected path through the course when following the existing course structure (Tang, Peterson, & Pardos, 2017). This work builds on the observation that patterns exist in learner clickstream behaviours.…”
Section: Representation Learning With Skip-gramsmentioning
confidence: 98%
“…In an online course context, the available input includes event stream (or clickstream) data which features inputs of mixed type. The output can be any logged outcome, such as certification in the course [23], stop-out [24,25] or predicting what action the learner is going to take next in the course [26 ]. In this case, behavior is the input and the output.…”
Section: Student Idmentioning
confidence: 99%